Modus Operandi Tindak Pidana Penggelapan Pajak Di Indonesia - Yonani, Yonani (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
People's contribution tax to the state treasury is based on the law without receiving any direct merit (contra-performance) which can be directly demonstrated and which is used to pay for public expenses. Tax crime by adding fictitious costs. Making a management contract with a group company abroad incurs management fees/technical fees/consultant costs. But actually, no service is performed. Then, to pay off the management fee/technical fee/consultant fee, funds will be transferred from the company account to the group company account abroad. The company will make costs or receipts where no costs are actually incurred, then the fictitious financing money will be transferred from the company to a temporary escrow account which will then be distributed to shareholders. By making a hedging or wash-out contract with a backdated date, the Taxpayer (WP) will always suffer a loss in the hedging or wash-out. Repayment of hedging/wash out losses will be transferred from the company account to the group company account abroad.